Exploring the factors influencing Unified Payments Interface (UPI) adoption among senior citizens in India - Shanmugasundaram, Roopesh Kumar (2024)
This research investigates the factors impacting Unified Payments Interface (UPI) adoption among the elderly in India. We conducted semi-structured interviews with 17 senior citizens in the Indian state of Tamil Nadu, where questions were developed based on themes from UTAUT2 constructs. The study identified both facilitators and challenges influencing UPI adoption among senior citizens. While some perceived trust in family members, perceived usefulness, social influence and policy mandate as significant determinants of UPI adoption, others express concerns about self-efficacy, their physical wellbeing and the system’s complexity. Moreover, the research underscores the importance of addressing the language barrier, lack of support and security concerns to promote UPI adoption among this segment of the population for financial inclusion in India. Based on the findings, recommendations are proposed for FinTech service providers to improve user experience and address senior-specific needs. Additionally, we propose for policy changes to promote awareness and support initiatives for the senior citizens demographic. This research contributes to the literature on internet banking adoption among the elderly, providing valuable insights that can be utilized by other developing nations. The insights developed from this study can inform the development of financial inclusion initiatives and equip businesses in tapping into the vast, yet underserved market segment of senior citizens.